1997
DOI: 10.1002/(sici)1096-8628(19971231)73:4<378::aid-ajmg2>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Carrier screening for cystic fibrosis: Test acceptance and one year follow-up

Abstract: We identified 124 carriers among 4,879 patients of prenatal care providers in the Rochester region. Six factors were identified that together permitted a correct classification regarding test acceptance for 77.5% of all subjects. For those pregnant, the most influential of these factors was a more accepting attitude toward abortion. As an indication for abortion, cystic fibrosis (CF) ranked between mild and moderate mental retardation. Of the 124 carrier women identified, we obtained 1-year follow-up informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…Similarly, another study found that nonpregnant women often cited that abortion and religious beliefs are important factors in the decision whether or not to have screening (Clayton et al 1996). In a number of studies that explored the reasons for declining CF carrier screening, all found that a main reason for declining screening was not intending to terminate a pregnancy (Cuckle et al 1996;Levenkron et al 1997;Livingstone et al 1993;Loader et al 1996;Mennie et al 1992). Of the participants who wished to be offered testing at another time, the majority would have liked to receive an offer of screening prior to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study found that nonpregnant women often cited that abortion and religious beliefs are important factors in the decision whether or not to have screening (Clayton et al 1996). In a number of studies that explored the reasons for declining CF carrier screening, all found that a main reason for declining screening was not intending to terminate a pregnancy (Cuckle et al 1996;Levenkron et al 1997;Livingstone et al 1993;Loader et al 1996;Mennie et al 1992). Of the participants who wished to be offered testing at another time, the majority would have liked to receive an offer of screening prior to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Non-pregnant women represented just 10% of those offered testing. Follow-up 1 year later suggested that "most of the adverse outcomes observed in this trial could have been avoided by more effective patient education by the primary care provider" (Levenkron et al 1997). In Victoria, Australia, CF carrier screening is offered as a feefor-service (AUD$200 per person) to women planning pregnancies and those in early pregnancy.…”
Section: Preconception Carrier Screening For Cf In Primary Carementioning
confidence: 96%
“…42,50,53,64,73 Individual carrier status did not affect reproductive intentions or behaviors, with carriers not altering their reproductive plans after receiving a positive test result. [65][66][67]71,73,[76][77][78] Screening of partners of carriers to determine risk of having a child with CF had an uptake of 61-100%, 20,36,52,74,[78][79][80][81][82][83] with reasons for partners not being tested being as follows: anxiety about result; would be tested when planning to start a family; would not alter reproductive plans; and had no further reproductive plans. 74,78 When participants were asked to consider their reproductive intentions if they were found to be a carrier couple, the majority stated that they would not have (more) children, 10,71 would utilize prenatal diagnosis in future pregnancies, 10,52,71 were unsure, or would not terminate an affected fetus.…”
Section: Outcomes and Follow-up Of Screening For Cf Carrier Statusmentioning
confidence: 99%
“…[65][66][67]71,73,[76][77][78] Screening of partners of carriers to determine risk of having a child with CF had an uptake of 61-100%, 20,36,52,74,[78][79][80][81][82][83] with reasons for partners not being tested being as follows: anxiety about result; would be tested when planning to start a family; would not alter reproductive plans; and had no further reproductive plans. 74,78 When participants were asked to consider their reproductive intentions if they were found to be a carrier couple, the majority stated that they would not have (more) children, 10,71 would utilize prenatal diagnosis in future pregnancies, 10,52,71 were unsure, or would not terminate an affected fetus. 23,52,57 In actuality, 80-100% of the carrier couples identified utilized prenatal diagnosis, 38,39,41,51,60,66,75,[78][79][80]82,84,85 and the majority terminated an affected fetus.…”
Section: Outcomes and Follow-up Of Screening For Cf Carrier Statusmentioning
confidence: 99%